Perovskite layer / hole transport layer composite film, perovskite silicon-based laminated solar cell and preparation method of perovskite silicon-based laminated solar cell

By using the perovskite layer/hole transport layer composite film technology in perovskite/silicon stacked batteries, the problem of uniform coverage of hole transport materials in large-area batteries is solved, and efficient charge transport and stable battery performance is achieved.

CN119836119APending Publication Date: 2025-04-15SUZHOU MAXWELL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411794731.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When preparing large-area perovskite/silicon stacked batteries, it is difficult to achieve uniformly covered hole transport materials, resulting in low battery efficiency.

Method used

A perovskite layer/hole transport layer composite film is used to form a laminated structure of perovskite layer and hole transport layer in situ by mixing it in situ. Annealing treatment is used to uniformly distribute the hole transport material at the buried interface and grain boundary of the perovskite.

Benefits of technology

The uniform coverage of the perovskite layer and the hole transport layer is achieved, the charge transfer efficiency of the battery is improved, the process flow is simplified, the cost is reduced, and the performance stability of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836119A_ABST
    Figure CN119836119A_ABST
Patent Text Reader

Abstract

The invention relates to the field of perovskite cells, in particular to a perovskite layer / hole transport layer composite film, a perovskite silicon-based laminated solar cell and preparation methods of the perovskite layer / hole transport layer composite film and the perovskite silicon-based laminated solar cell. The perovskite layer / hole transport layer composite film comprises a perovskite layer and a hole transport layer which are adjacent to each other; and a part of the hole transport layer is embedded at the grain boundary of the crystals of the perovskite layer. The preparation method of the composite film comprises the following steps: dissolving a perovskite precursor and a hole transport material in an organic solvent to obtain a mixed solution of the perovskite precursor and the hole transport material; and carrying out film coating treatment on the mixed solution of the perovskite precursor and the hole transport material, and annealing to form the perovskite layer / hole transport layer composite film. The perovskite layer / hole transport layer composite film and the perovskite silicon-based laminated solar cell are simple in preparation process, high in cell efficiency and stable in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of perovskite cells, and in particular to a perovskite layer / hole transport layer composite film and a perovskite silicon-based stacked solar cell and a preparation method thereof. Background Art

[0002] Perovskite silicon-based tandem solar cells are a type of high-efficiency photovoltaic device that combines the advantages of perovskite materials and single-crystal silicon materials. They mainly include the following three parts: a silicon base cell, a perovskite top cell, and a transparent conductive layer or tunnel junction between the silicon base cell and the perovskite top cell. Perovskite silicon-based tandem solar cells achieve a wider range of solar spectrum absorption by stacking two materials with different photoelectric properties. The silicon base cell uses its mature technology and suitable band gap to absorb photons in the near-infrared region, while the perovskite top cell effectively absorbs photons in the visible light region due to its wide band gap characteristics, reducing energy loss caused by thermal relaxation. The two layers of cells are connected by an electron tunnel junction or a transparent conductive layer, which not only achieves current matching, but also improves the open circuit voltage of the entire cell through the principle of voltage superposition, thus breaking through the efficiency limit of traditional single-junction solar cells.

[0003] Perovskite silicon-based tandem solar cells have shown significant efficiency and cost advantages due to their unique structure and material combination. The theoretical efficiency limit of perovskite silicon-based tandem solar cells is much higher than that of single-junction perovskite solar cells and crystalline silicon cells, and this tandem design also has the advantage of being compatible with existing crystalline silicon component processes, which helps reduce additional costs and is expected to further reduce the cost per kilowatt-hour.

[0004] Although the prospects of perovskite-silicon tandem solar cells are very promising, there are still some challenges before they can be widely industrialized. 2 ) The preparation of relatively small-area stacked cells is much more difficult. One of the reasons is that due to the velvet structure of silicon cells, it is difficult to evenly cover the thin hole transport material on the surface of the silicon wafer using the solution method. In addition, the hole transport material is generally highly hydrophobic, and the perovskite solution has poor fluidity on its surface, which is prone to non-wetting, resulting in low efficiency of large-area stacked cells.

[0005] Based on this, it is necessary to develop a perovskite silicon-based tandem solar cell with simple process and higher cell efficiency. Summary of the invention

[0006] Based on this, one or more embodiments of the present application provide a perovskite layer / hole transport layer composite film and a perovskite silicon-based tandem solar cell and a preparation method thereof. The perovskite layer / hole transport layer composite film and the perovskite silicon-based tandem solar cell of the present application have a simple preparation process, high cell efficiency and stable performance.

[0007] The technical solution of this application includes the following contents:

[0008] A perovskite layer / hole transport layer composite film, characterized in that it is prepared by subjecting a mixed solution including a perovskite precursor material, a hole transport material and an organic solvent to a film-forming treatment and then to an annealing treatment, wherein the perovskite layer / hole transport layer composite film comprises a perovskite layer and a hole transport layer adjacent to each other; wherein,

[0009] The hole transport material includes an organic hole transport material;

[0010] The perovskite layer composition includes ABX3 type perovskite material, wherein: the A-site ions include CH3NH3 + 、CH(NH2)2 + 、(CH3)2NH2 + , Cs + , Tl + Sc 3+ and Y 3+ At least one of; B site ions include Pb 2+ Sn 2+ ,Ge 2+ 、Ti 4+ and Zr 4+ At least one of; X-site ions include Br - ,I - , Cl - and SCN - At least one of .

[0011] In some embodiments, the organic hole transport material is a carbazole phosphate hole transport material.

[0012] In some embodiments, the thickness of the perovskite layer is 500nm~1200nm, and the thickness of the hole transport layer is 2nm~10nm.

[0013] In some embodiments, the organic hole transport material includes at least one of 2-(7H-dibenzo[c, g]carbazole-7-yl)ethylamine, 4-(7H-dibenzo[c, g]carbazole-7-yl)butylamine, 2-methoxy-2-(7H-dibenzo[c, g]carbazole-7-yl)ethylamine, 4-methoxy-4-(7H-dibenzo[c, g]carbazole-7-yl)butylamine and (4-(7H-dibenzo[c, g]carbazole-7-yl)butyl)phosphonic acid; and / or,

[0014] The organic solvent includes at least one of dimethylformamide, dimethyl sulfoxide, acrylonitrile, N-methylpyrrolidone, butanediol, dimethylamine, dimethylimine and 2-methoxyethanol.

[0015] In some embodiments, the annealing conditions include:

[0016] The annealing treatment is carried out in a cavity having an exhaust system and an air inlet system, and heat-treated nitrogen is introduced through the air inlet system, and the gas containing water vapor and organic solvent in the cavity is discharged through the exhaust system; the heat-treated nitrogen refers to nitrogen with a temperature of 100°C to 150°C.

[0017] A method for preparing the above-mentioned perovskite layer / hole transport layer composite film comprises:

[0018] Dissolving the perovskite precursor material and the hole transport material in the organic solvent to obtain a mixed solution;

[0019] The mixed liquid is subjected to film-forming treatment to obtain a wet film;

[0020] The wet film is subjected to annealing treatment to obtain a perovskite layer / hole transport layer composite film.

[0021] In some embodiments, the step of preparing a wet film by subjecting the mixed liquid to a film-forming treatment comprises:

[0022] The mixed liquid is subjected to film coating treatment to obtain a wet film;

[0023] Optionally, the coating method includes at least one of inkjet printing, slit coating, blade coating and immersion;

[0024] Optionally, the wet film has a thickness of 8 μm to 12 μm.

[0025] In some embodiments, the step of preparing a perovskite layer / hole transport layer composite film by annealing the wet film comprises:

[0026] Placing the wet film in a cavity having an air inlet system and an air exhaust system, wherein the air inlet system is used to pass the heat-treated nitrogen into the annealing cavity, and the air exhaust system is used to remove the gas containing water vapor and organic solvent in the cavity;

[0027] The heat-treated nitrogen refers to nitrogen at a temperature of 100° C. to 150° C.

[0028] A perovskite silicon-based tandem solar cell, comprising a silicon base cell, a perovskite top cell and an intermediate layer between the silicon base cell and the perovskite top cell, wherein the perovskite top cell comprises the perovskite layer / hole transport layer composite film described above;

[0029] Wherein, the velvet surface of the silicon substrate cell is adjacent to the intermediate layer;

[0030] The hole transport layer in the perovskite layer / hole transport layer composite film is adjacent to the intermediate layer.

[0031] A method for preparing a perovskite silicon-based tandem solar cell, comprising:

[0032] Prepare an intermediate layer on the velvet surface of the silicon substrate battery;

[0033] The hole transport layer and the perovskite layer are prepared in one step on the intermediate layer by using the method for preparing the perovskite layer / hole transport layer composite film described above;

[0034] The functional layers of the perovskite silicon-based tandem solar cell are sequentially prepared on the perovskite layer.

[0035] SHJ cells, Heterojunction with Intrinsic Thin layer (HIT) cells, are high-efficiency solar cells constructed with amorphous silicon and crystalline silicon materials. Compared with traditional crystalline silicon solar cells, SHJ cells have higher photoelectric conversion efficiency and better low-light performance. SHJ cells are generally based on N-type silicon wafers. In order to increase light capture and reduce reflection, the surface of the substrate is chemically treated to form a velvet structure. This structure is composed of tiny pyramids that can scatter incident light, increase the path length of light, and thus improve light absorption.

[0036] In the traditional preparation method of perovskite silicon-based stacked solar cells, the hole transport layer and the perovskite layer are prepared in steps. Since the main function of the hole transport layer is to transfer the holes generated in the perovskite layer to the anode, the thinner layer thickness can reduce the recombination loss of holes during the transmission process and improve the hole extraction efficiency of the battery. At the same time, it can also ensure that the upper battery can receive enough light to avoid absorbing the photons that should have been absorbed by the active layer. Therefore, the thickness of the hole transport layer is usually set between 20nm and 200nm. Such a thickness requirement makes it difficult for the hole transport layer to form a uniform coverage on the pyramid. The material of the hole transport layer is usually highly hydrophobic, and the perovskite solution has poor fluidity on its surface, making it difficult to form a uniform coverage on the hole transport layer. Therefore, the traditional preparation method is prone to unevenness and exposure of the velvet pyramid, the preparation process has poor repeatability, and the performance of the resulting battery is unstable.

[0037] The perovskite layer / hole transport layer composite film of the present application is a stacked structure of a perovskite layer and a hole transport layer generated in situ by one-step mixing. The use of the composite film to prepare a perovskite cell solves the problem of difficulty in achieving uniform coverage by first preparing the hole transport layer and then the perovskite layer. In addition, since the hole material in the composite film is uniformly distributed at the buried interface and grain boundaries of the perovskite, the composite film has basically the same electron transport effect as a traditional hole transport perovskite stack.

[0038] After the hole transport layer is prepared by the traditional method, the hole transport material will gather at the bottom of the pyramid valley, and because the hole transport material is hydrophobic, it is difficult for the perovskite to be evenly distributed on the hole transport layer, resulting in the exposure of the pyramid. Compared with the traditional method of preparing the hole transport layer and the perovskite layer separately, the method of preparing the perovskite layer / hole transport layer composite film by a one-step mixed coating in the present application has a better film-forming effect. On the one hand, the surface of the attachment surface of the present application is not first covered with a hole transport layer, and the mixed liquid containing perovskite can better achieve infiltration on the surface. On the other hand, the hole transport material can be evenly distributed in the mixed liquid, achieving uniform dispersion, and in the annealing stage, due to the large molecular radius of the hole transport material, it will be squeezed out by the perovskite lattice during the perovskite crystallization process to be distributed at the buried interface and grain boundary, which is equivalent to forming a hole transport layer at the buried interface. At the same time, the embedding of the hole transport material also passivates some grain boundary defects of the perovskite film, achieving multiple goals at one stroke.

[0039] The perovskite silicon-based tandem solar cell of the present application uses a perovskite top cell having the perovskite layer / hole transport layer composite film, which simplifies the process flow and greatly reduces the difficulty of uniformly covering the hole transport material and perovskite on the velvet pyramid. The operation is simpler and the cost is lower. The obtained perovskite silicon-based tandem solar cell also has good cell transmission efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0041] Figure 1 Schematic diagram of the structure of a traditional perovskite silicon-based tandem solar cell;

[0042] Figure 2 This is a flow chart of the preparation process of traditional perovskite silicon-based tandem solar cells;

[0043] Figure 3This is a process flow chart of preparing a perovskite silicon-based tandem solar cell according to an embodiment of the present application;

[0044] Figure 4 A schematic diagram of an annealing device for a perovskite layer / hole transport layer composite film according to an embodiment of the present application;

[0045] Figure 5 A comparison result of the appearance of a hole transport perovskite stack prepared by a conventional method in the present application and the appearance of a perovskite layer / hole transport layer composite film prepared in an embodiment of the present application;

[0046] Figure 6 The comparison results of the SEM images of the white spots and the normal positions of the hole transport perovskite stack prepared by the conventional method in this application are shown in FIG.

[0047] Figure 7 A comparison result of the appearance of a hole transport perovskite stack prepared by a conventional method in the present application and the appearance of a perovskite layer / hole transport layer composite film prepared in an embodiment of the present application;

[0048] Figure 8 The comparison result of the PL image of the hole transport perovskite stack prepared by the traditional method and the PL image of the perovskite layer / hole transport layer composite film prepared by an embodiment of the present application is shown in FIG.

[0049] Markings in the figure are: 100, loading chamber; 200, annealing chamber; 300, unloading chamber; 400, exhaust system; 500, air intake system; 600, flow meter; 210, carrier. DETAILED DESCRIPTION

[0050] The present application will be further described below in conjunction with the embodiments and examples. It should be understood that these examples are only used to illustrate the present application and are not intended to limit the scope of the present application. In addition, it should be understood that after reading the content taught in the present application, those skilled in the art may make various changes or modifications to the present application, and these equivalent forms also fall within the protection scope of the claims attached to the present application.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0052] the term

[0053] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0054] The term "and / or" used in this article includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in this application, the technical solution undoubtedly includes technical solutions that are all connected by "logical and", and undoubtedly includes technical solutions that are all connected by "logical or". For example, "A and / or B" includes three parallel solutions of A, B and A+B. For example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution that is all connected by "logical OR"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four of A, B, C, and D (that is, the technical solution that is all connected by "logical AND").

[0055] Herein, "preferred", "preferable", "better", etc. are only used to describe implementation methods or examples with better effects. It should be understood that they do not constitute limitations on the scope of protection of this application.

[0056] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0057] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0058] In this application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.

[0059] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0060] In the present application, weight may be μg, mg, g, kg or other mass units known in the chemical industry.

[0061] The technical solution of the present application is proposed under the following background: the existing method for preparing perovskite silicon-based tandem solar cells is usually to first prepare a very thin hole transport layer on the transparent conductive layer of the silicon cell by a wet method, and its thickness is only a few nanometers, and then prepare a layer of perovskite wet film on the basis of the hole transport layer, the wet film thickness is between a few microns and more than ten microns, and the dry film thickness after drying and annealing is between several hundred nanometers and more than one micron. The ultra-thin hole transport layer has poor coverage uniformity on the velvet structure, and the hole transport layer generally has strong hydrophobicity. The perovskite solution has poor fluidity on its surface, and it is easy to not wet and expose the velvet pyramid, resulting in unstable performance of the tandem battery and poor repeatability.

[0062] In order to solve the above problems, one aspect of the present application provides a perovskite layer / hole transport layer composite film, which is prepared by subjecting a mixed liquid including a perovskite precursor, a hole transport material and an organic solvent to a film-forming treatment and then to an annealing treatment;

[0063] Hole transport materials include organic hole transport materials;

[0064] The perovskite layer / hole transport layer composite film includes a perovskite layer and a hole transport layer adjacent to each other.

[0065] Compared with the stacked layers prepared by the traditional method of first preparing the hole transport layer and then coating the perovskite, the perovskite layer / hole transport layer composite film of the present application has a more complete layer structure and the two layers are more closely connected. A portion of the hole transport layer is embedded in the crystal grain boundaries of the perovskite layer, which passivates some of the grain boundary defects of the perovskite layer and can more effectively inhibit electron-hole recombination.

[0066] In the perovskite layer / hole transport layer composite film of the embodiment of the present application, the perovskite layer composition includes ABX3 type perovskite material. In the chemical structure shown in ABX3, the A-site ion is a cation, which can be a mixture of organic ions and inorganic ions, or a pure organic or inorganic ion. The B-site ion is a cation with a smaller radius, and the X-site ion is an anion.

[0067] In some embodiments, the A-site ions are selected from monovalent cations, the B-site ions are selected from divalent cations, the X-site ions are selected from halogen anions, and the ratio of the total molar amount of the A-site ions, the total molar amount of the B-site ions and the total molar amount of the X-site ions is 1:1:3, so that ABX3-type perovskite crystals can be formed.

[0068] In this embodiment, the A-site ions include CH3NH3 + 、CH(NH2)2 + 、(CH3)2NH2 + , Cs + and Tl + At least one of; B site ions include Pb 2+ Sn 2+ and Ge 2+ At least one of; X-site ions include Br - ,I - , Cl - and SCN - At least one of .

[0069] It is understandable that other doping ions may be present in the perovskite precursor material.

[0070] In the perovskite layer / hole transport layer composite film of the embodiment of the present application, the organic hole transport material is a carbazole phosphate hole transport material.

[0071] Optionally, the organic hole transport material includes at least one of 2-(7H-dibenzo[c, g]carbazole-7-yl)ethylamine, 4-(7H-dibenzo[c, g]carbazole-7-yl)butylamine, 2-methoxy-2-(7H-dibenzo[c, g]carbazole-7-yl)ethylamine, 4-methoxy-4-(7H-dibenzo[c, g]carbazole-7-yl)butylamine and (4-(7H-dibenzo[c, g]carbazole-7-yl)butyl)phosphonic acid.

[0072] Optionally, the organic solvent includes at least one of dimethylformamide, dimethyl sulfoxide, acrylonitrile, N-methylpyrrolidone, butanediol, dimethylamine, dimethylimine and 2-methoxyethanol.

[0073] The perovskite layer / hole transport layer composite film of the embodiment of the present application is prepared by subjecting a mixed liquid including a perovskite precursor, a hole transport material and an organic solvent to a film-forming treatment and then to an annealing treatment.

[0074] In some embodiments, the annealing conditions include:

[0075] Annealing is carried out in a cavity having an exhaust system and an air inlet system, and heat-treated nitrogen is introduced through the air inlet system, and the gas containing water vapor and organic solvents in the cavity is removed through the exhaust system; the heat-treated nitrogen refers to nitrogen with a temperature of 100°C to 150°C.

[0076] In some embodiments, in the perovskite layer / hole transport layer composite film of the embodiments of the present application, the thickness of the perovskite layer is 500nm~1200nm, and the thickness of the hole transport layer is 2nm~10nm.

[0077] In yet another aspect of the present application, a method for preparing a perovskite layer / hole transport layer composite film is provided, which can be used to prepare the above perovskite layer / hole transport layer composite film.

[0078] The preparation method of the perovskite layer / hole transport layer composite film of the present application can be used to prepare the hole transport layer and the perovskite layer in one step on a pyramid-shaped velvet structure, solving the problem that it is difficult to achieve uniform coverage by first preparing the hole transport layer and then preparing the perovskite layer. On the one hand, the surface of the attachment surface of the present application is not covered with the hole transport layer first, and the mixed liquid containing perovskite can better achieve infiltration on the surface. On the other hand, the hole transport material can be evenly distributed in the mixed liquid to achieve uniform dispersion. Moreover, in the annealing stage, due to the large molecular radius of the hole transport material, it will be squeezed out by the perovskite lattice during the perovskite crystallization process to form a hole transport layer and distributed at the grain boundaries of the perovskite, thereby passivating some grain boundary defects of the perovskite film.

[0079] The method for preparing a perovskite layer / hole transport layer composite film according to an embodiment of the present application comprises:

[0080] Dissolving a perovskite precursor and the hole transport material in the organic solvent to obtain a mixed solution;

[0081] The mixed liquid is subjected to film-forming treatment to obtain a wet film;

[0082] The wet film is annealed to obtain a perovskite layer / hole transport layer composite film.

[0083] Optionally, the perovskite precursor includes A-site ions, B-site ions and X-site ions, and the definitions and theoretical molar ratios of the A-site ions, the B-site ions and the X-site ions are as described above.

[0084] Preferably, the organic solvent meets the following conditions: ① strong solubility, especially for lead halide; ② will not react with lead ions to form a complex; ③ the boiling point of the organic solvent should be as low as possible when conditions ① and ② are met, and the saturated vapor pressure should be as high as possible when conditions ① and ② are met.

[0085] Optionally, the organic solvent includes at least one of dimethylformamide, dimethyl sulfoxide, acrylonitrile, N-methylpyrrolidone, butanediol, dimethylamine, dimethylimine and 2-methoxyethanol.

[0086] Optionally, the hole transport material includes at least one of 2-(7H-dibenzo[c, g]carbazole-7-yl)ethylamine, 4-(7H-dibenzo[c, g]carbazole-7-yl)butylamine, 2-methoxy-2-(7H-dibenzo[c, g]carbazole-7-yl)ethylamine, 4-methoxy-4-(7H-dibenzo[c, g]carbazole-7-yl)butylamine and (4-(7H-dibenzo[c, g]carbazole-7-yl)butyl)phosphonic acid.

[0087] Optionally, the molar ratio of the B-site ion to the hole transport material is 10:(0.02-0.1).

[0088] In some embodiments, the step of preparing a wet film by subjecting the mixed liquid to a film-forming treatment comprises:

[0089] The mixed liquid is subjected to film coating treatment to obtain a wet film;

[0090] Optionally, the coating method includes at least one of inkjet printing, slit coating, blade coating and immersion.

[0091] Optionally, the thickness of the wet film is 8 μm to 12 μm. At this thickness, the mixed liquid can be evenly coated on various attachment surfaces that may be involved in the stacked battery in a simple manner, for example, evenly coated on the velvet surface of the silicon substrate battery with a pyramid structure.

[0092] In the field of perovskite cells, traditional thin film annealing processes are usually implemented in high-temperature chambers. For large-area thin films, since annealing is carried out in a high-temperature chamber, a large amount of water vapor and oxygen will enter the chamber when the chamber gate valve is opened. When annealing is performed with the gate valve closed, it will affect the crystallization of the film. After annealing, the surface color will be uneven, affecting the efficiency of the stacked cell. In addition, the solvent evaporates into gas during the annealing process and will remain in the closed chamber, which will have a great impact on the crystallization quality of the perovskite.

[0093] In some embodiments of the present application, the step of preparing a perovskite layer / hole transport layer composite film by annealing the wet film includes:

[0094] The wet film is placed in a cavity having an air inlet system and an air exhaust system, wherein the air inlet system is used to pass the heat-treated nitrogen into the annealing cavity, and the air exhaust system is used to remove the gas containing water vapor and organic solvent in the cavity;

[0095] The heat-treated nitrogen refers to nitrogen at a temperature of 100°C to 150°C, which is the same as the heating temperature of the high-temperature cavity, further reducing the effect of the heat-treated nitrogen on the uniformity of perovskite crystallization.

[0096] Compared with direct high-temperature annealing, the annealing method in this embodiment adopts the method of introducing heat-treated nitrogen while exhausting the gas in the cavity. The surface color of the perovskite after annealing is more uniform and smooth. This is mainly because the introduction of heat-treated nitrogen and then exhausting it can take away the moisture and oxygen in the cavity, avoiding the negative effects of water and oxygen on the perovskite, and can also take away the volatile residual solvent to avoid affecting the crystallization of the perovskite.

[0097] Specifically, the exhaust system includes an exhaust fan, which removes gas containing water vapor and residual organic solvents in the cavity, and the air inlet system is used to pass heated nitrogen into the annealing cavity to further ensure that the wet film obtains better perovskite crystallization.

[0098] Optionally, the flow rate of nitrogen after heat treatment is 1500 sccm~2500 sccm.

[0099] Optionally, the annealing time is 10 min to 30 min.

[0100] Optionally, the flow rate of the heat-treated nitrogen gas introduced into the high-temperature cavity can be controlled by a flow meter, and the exhaust rate can be controlled by controlling the power of the exhaust system. The exhaust rate can be adaptively adjusted according to the flow rate of the heat-treated nitrogen gas introduced.

[0101] The above annealing process can obtain better quality perovskite crystals. Perovskite films with high crystal quality can absorb sunlight more effectively and reduce the recombination of carriers, which is beneficial to improving the photoelectric conversion efficiency of the battery. High-quality crystals also have better charge transfer characteristics, allowing electrons and holes to move more efficiently in perovskite materials and reduce energy loss.

[0102] Compared with direct high-temperature annealing, the annealing method of one embodiment of the present application has a wider range of applications and is suitable for large-scale industrial production of thin films. Since the heating chamber is relatively large in size for industrialization, the temperature uniformity in the chamber is poor. The introduction of heat-treated nitrogen can make the temperature in the chamber more uniform, and the color of the perovskite film is uniform after film formation.

[0103] As an example, the retreat method of an embodiment of the present application is suitable for preparing large-area thin films, for example, thin film preparation for silicon wafers of 166mm×166mm, 182mm×182mm, and 210mm×105mm in size can be achieved.

[0104] An embodiment of the present application further provides a perovskite silicon-based tandem solar cell, comprising a silicon base cell, a perovskite top cell, and an intermediate layer between the silicon base cell and the perovskite top cell, wherein the perovskite top cell comprises a perovskite layer / hole transport layer composite film and a functional layer of the present application;

[0105] Among them, the velvet surface of the silicon base cell is adjacent to the middle layer;

[0106] The hole transport layer in the perovskite layer / hole transport layer composite film is adjacent to the intermediate layer.

[0107] In the perovskite silicon-based tandem solar cell of the present application, the intermediate layer may include a transparent conductive layer, a tunnel junction layer, etc.; the functional layer may include a passivation layer, an electron transport layer, a buffer layer, a TCO, an electrode, etc.

[0108] The perovskite silicon-based tandem solar cell of one embodiment of the present application includes, from bottom to top, a bottom electrode, a silicon-based cell, an intermediate layer, a perovskite layer / hole transport layer composite film, a passivation layer, an electron transport layer, a buffer layer, a transparent conductive layer and a top electrode, wherein the perovskite layer / hole transport layer composite film includes a perovskite layer and a hole transport layer adjacent to each other; the velvet surface of the silicon-based cell is adjacent to the intermediate layer; and the hole transport layer in the perovskite layer / hole transport layer composite film is adjacent to the intermediate layer.

[0109] In some embodiments, other functional layers, such as an anti-reflection layer, are provided between the transparent conductive layer and the top electrode.

[0110] In some embodiments, the perovskite silicon-based tandem solar cell includes, from bottom to top, a bottom electrode, a silicon base cell, an intermediate layer, a perovskite layer / hole transport layer composite film, a passivation layer, an electron transport layer, a buffer layer, a transparent electrode layer, an anti-reflection layer and a top electrode.

[0111] Optionally, the thickness of the intermediate layer is 10 nm to 50 nm.

[0112] Optionally, the thickness of the perovskite layer / hole transport layer composite film is 500nm~1200nm.

[0113] Optionally, the thickness of the passivation layer is 1 nm to 10 nm.

[0114] Optionally, the thickness of the electron transport layer is 10 nm to 50 nm.

[0115] Optionally, the buffer layer has a thickness of 10 nm to 50 nm.

[0116] Optionally, the thickness of the transparent electrode layer is 100nm-200nm.

[0117] Optionally, the thickness of the anti-reflection layer is 100 nm to 200 nm.

[0118] An embodiment of the present application further provides a method for preparing a perovskite silicon-based tandem solar cell, comprising:

[0119] Prepare an intermediate layer on the velvet surface of the silicon substrate battery;

[0120] The hole transport layer and the perovskite layer are prepared in one step on the intermediate layer by using the preparation method of the perovskite layer / hole transport layer composite film of any of the above technical solutions;

[0121] The functional layers of the perovskite silicon-based tandem solar cell are sequentially prepared on the perovskite layer.

[0122] In one embodiment, a method for preparing a perovskite silicon-based tandem solar cell comprises:

[0123] Prepare an intermediate layer on the velvet surface of the silicon substrate battery;

[0124] Dissolving a perovskite precursor and a hole transport material in an organic solvent to obtain a mixed solution of the perovskite precursor and the hole transport material, coating the mixed solution of the perovskite precursor and the hole transport material on the intermediate layer to obtain a wet film, and annealing the wet film to form a perovskite layer / hole transport layer composite film, wherein the hole transport layer in the perovskite layer / hole transport layer composite film is adjacent to the intermediate layer, exposing the perovskite layer;

[0125] A passivation layer, an electron transport layer, a buffer layer, a transparent electrode and an anti-reflection layer are sequentially prepared on the perovskite layer;

[0126] Furthermore, a bottom electrode and a top electrode are connected.

[0127] The preparation method of the perovskite silicon-based tandem solar cell of the present application simplifies the process flow and greatly reduces the difficulty of uniformly covering the hole transport material and the perovskite on the velvet pyramid. The operation is simpler and the cost is lower. The prepared perovskite silicon-based tandem solar cell also has good cell transmission efficiency.

[0128] The perovskite silicon-based tandem solar cell of the present application has a relatively high cell efficiency, for example, can reach about 26.5%.

[0129] The following is an explanation with a schematic diagram:

[0130] As mentioned above, conventional perovskite silicon-based tandem solar cells are usually prepared layer by layer on a silicon substrate cell, see Figure 1 , Figure 1 This is a schematic diagram of the structure of a traditional perovskite silicon-based tandem solar cell, which includes, from bottom to top, a bottom electrode, a silicon base cell, an intermediate layer, a hole transport layer, a perovskite layer, a passivation layer, an electron transport layer, a buffer layer, a transparent conductive layer, and a top electrode. Figure 2 , Figure 2 This is a flow chart of the preparation process of traditional perovskite silicon-based tandem solar cells, in which the hole transport layer and the perovskite layer are prepared in a distributed manner.

[0131] The perovskite silicon-based tandem solar cell of the present application is obtained by preparing a perovskite layer / hole transport layer composite film in one step after preparing an intermediate layer on a silicon-based cell, preparing a hole transport layer and a perovskite layer at the same time, and then preparing layer by layer on the perovskite layer / hole transport layer composite film; wherein the perovskite layer / hole transport layer composite film includes a perovskite layer and a hole transport layer adjacent to each other; the velvet surface of the silicon-based cell is adjacent to the intermediate layer; the hole transport layer in the perovskite layer / hole transport layer composite film is adjacent to the intermediate layer; see Figure 3 , Figure 3 This is a process flow chart for preparing a perovskite silicon-based stacked solar cell according to an embodiment of the present application. The process not only saves steps, but also solves the problem that it is difficult to achieve uniform coverage by first preparing a hole transport layer and then preparing a perovskite layer. On the one hand, the surface of the attachment surface of the present application is not covered with a hole transport layer first, and the mixed liquid containing perovskite can better achieve infiltration on the surface. On the other hand, the hole transport material can be evenly distributed in the mixed liquid to achieve uniform dispersion. Moreover, in the annealing stage, due to the large molecular radius of the hole transport material, it will be squeezed out by the perovskite lattice during the perovskite crystallization process so that it is distributed in the bottom layer to form a hole transport layer and distributed at the grain boundaries of the perovskite, thereby passivating some grain boundary defects of the perovskite film.

[0132] See also Figure 4 In the preparation process of the perovskite layer / hole transport layer composite film of an embodiment of the present application, the device used for annealing includes a loading chamber 100, an annealing chamber 200, a unloading chamber 300, an exhaust system 400, an air inlet system 500 and a flow meter 600. The loading chamber 100 is used for feeding, and the annealing chamber 200 is used for annealing. A carrier 210 is provided in the annealing chamber 200 for placing materials to be annealed, and the unloading chamber 300 is used for temporarily placing the annealed materials for easy removal after cooling; the exhaust system 400 is used to exhaust the gas in the annealing chamber 200, the air inlet system 500 is used to introduce gas into the annealing chamber 200, and the flow meter 600 is used to detect the flow of the gas introduced through the air inlet system 500, so as to facilitate flow control.

[0133] The following are some specific embodiments.

[0134] For experimental parameters not specified in the following specific embodiments, reference is made to the instructions given in the present application document, and reference may also be made to experimental manuals in the art or other experimental methods known in the art, or to experimental conditions recommended by manufacturers.

[0135] The raw materials and reagents involved in the following specific examples can be obtained from commercial sources, or can be prepared by those skilled in the art according to known methods.

[0136] 1. Product preparation

[0137] Embodiment 1:

[0138] Step 1: Prepare an ITO composite layer of about 20nm on the front side of the SHJ bottom cell.

[0139] Step 2: 1 mmol of CsI, 9 mmol of FAI, 2 mmol of PbBr2, 8 mmol of PbI2, and 0.05 mmol of 4PADCB ([4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid) were added to a mixed solvent of DMF and NMP, with a volume ratio of DMF to NMP of 10:1 and a total volume of 10 ml, to fully dissolve the mixture and prepare a mixed precursor solution of perovskite and hole transport layer;

[0140] A 10 μm perovskite wet film was prepared by slit coating, and a nitrogen air knife was used to blow it dry during coating;

[0141] After the perovskite wet film is dried, it is transferred to a high-temperature chamber for annealing for 10 minutes. During annealing, 150°C nitrogen is introduced, and the nitrogen flow rate after heat treatment is controlled by a flow meter to be 2000sccm. At the same time, the exhaust fan power is set to 50% (50% of the maximum power). After annealing for 10 minutes, the film is transferred out of the annealing chamber to obtain a 1000nm composite film.

[0142] Step 3: Prepare a passivation layer. After annealing, use thermal evaporation to prepare a 1 nm LiF layer.

[0143] Step 4: Prepare an electron transport layer by using a thermal evaporation method to prepare a 10 nm C60 layer.

[0144] Step 5: Prepare a buffer layer and use ALD to prepare a 20nm SnO2 layer.

[0145] Step 6: Prepare a transparent electrode and use magnetron sputtering to prepare a 100nm ITO layer.

[0146] Step 7: Prepare Ag electrode and prepare silver grid line by screen printing.

[0147] Step 8: Prepare an anti-reflection layer and use thermal evaporation to prepare a 100nm MgF2 layer.

[0148] Step 9: Connect the bottom and top electrodes.

[0149] Example 2

[0150] Step 1: Prepare an ITO composite layer of about 20nm on the front side of the SHJ bottom cell.

[0151] Step 2: 1 mmol of CsI, 9 mmol of FAI, 2 mmol of PbBr2, 8 mmol of PbI2, and 0.05 mmol of MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid) were added to a mixed solvent of DMF and NMP, with a volume ratio of DMF to NMP of 10:1 and a total volume of 10 ml, to fully dissolve the mixture and prepare a mixed precursor solution of perovskite and hole transport layer;

[0152] A 10 μm perovskite wet film was prepared by slit coating, and a nitrogen air knife was used to blow it dry during coating;

[0153] After the perovskite wet film is dried, it is transferred to a high-temperature chamber for annealing for 10 minutes. During annealing, 150°C nitrogen is introduced, and the nitrogen flow rate after heat treatment is controlled by a flow meter to be 2000sccm. At the same time, the exhaust fan power is set to 50% (50% of the maximum power). After annealing for 10 minutes, the film is transferred out of the annealing chamber to obtain a 1000nm composite film.

[0154] Step 3: Prepare a passivation layer. After annealing, use thermal evaporation to prepare a 1 nm LiF layer.

[0155] Step 4: Prepare an electron transport layer by using a thermal evaporation method to prepare a 10 nm C60 layer.

[0156] Step 5: Prepare a buffer layer and use ALD to prepare a 20nm SnO2 layer.

[0157] Step 6: Prepare a transparent electrode and use magnetron sputtering to prepare a 100nm ITO layer.

[0158] Step 7: Prepare Ag electrode and prepare silver grid line by screen printing.

[0159] Step 8: Prepare an anti-reflection layer by using thermal evaporation to prepare 100nm MgF2.

[0160] Step 9: Connect the bottom and top electrodes.

[0161] Comparative Example 1

[0162] Step 1: Prepare an ITO composite layer of about 20nm on the front side of the SHJ bottom cell.

[0163] Step 2: 0.05 mmol of 4PADCB was added into a mixed solvent of DMF and NMP, and a 10 nm hole transport layer was prepared on the ITO composite layer by blade coating.

[0164] Step 3: Add 1 mmol of CsI, 9 mmol of FAI, 2 mmol of PbBr2, and 8 mmol of PbI2 into a mixed solvent of DMF and NMP, with a volume ratio of DMF to NMP of 10:1 and a total volume of 10 ml, to fully dissolve them;

[0165] A 10 μm perovskite wet film was prepared by slit coating, and a nitrogen air knife was used to blow it dry during coating;

[0166] After the perovskite wet film is dried, it is transferred to a high-temperature chamber for annealing for 10 minutes. During annealing, 150°C nitrogen is introduced, and the nitrogen flow rate after heat treatment is controlled by a flow meter to be 2000sccm. At the same time, the exhaust fan power is set to 50% (50% of the maximum power). After annealing for 10 minutes, the film is transferred out of the annealing chamber to obtain a 1000nm perovskite layer.

[0167] Step 4: Prepare a passivation layer. After annealing, use thermal evaporation to prepare a 1 nm LiF layer.

[0168] Step 5: Prepare the electron transport layer by using thermal evaporation method to prepare a 10 nm C60 layer.

[0169] Step 6: Prepare a buffer layer and use ALD to prepare a 20nm SnO2 layer.

[0170] Step 7: Prepare a transparent electrode and use magnetron sputtering to prepare a 100nm ITO layer.

[0171] Step 8: Prepare Ag electrode and prepare silver grid line by screen printing.

[0172] Step 9: Prepare an anti-reflection layer and use thermal evaporation to prepare a 100nm MgF2 layer.

[0173] Step 10: Connect the bottom and top electrodes.

[0174] 2. Performance Characterization

[0175] 1. Morphology characterization

[0176] See also Figure 5 , Figure 5 The appearance of a comparative hole transport layer and perovskite layer stacked film (left) and a hole transport layer / perovskite layer composite film (right) of an embodiment of the present application under the same annealing conditions. The surface of the comparative stacked film shows dotted white spots. The white spots mean that there may be a large number of pyramids exposed in the area, which may be caused by the poor wettability of the perovskite solution on the hole transport layer. The white spots may cause the device to have lower Voc and FF. The perovskite layer / hole transport layer composite film of the present application has no white spots.

[0177] See also Figure 6 , Figure 6 The comparison results of SEM images of white spots and normal positions. The SEM images verify the above hypothesis. It can be seen intuitively that there are a large number of pyramids exposed in the white spots.

[0178] PL, or photoluminescence (PL) spectrum, is an important technology used to detect and characterize the photoelectric properties of photovoltaic cell materials. By measuring the luminescence properties of materials under light excitation, PL can obtain important parameters such as the material's carrier lifetime, recombination rate, and defect level.

[0179] See also Figure 7 , Figure 7 This is the appearance of the hole transport layer / perovskite layer composite film of one embodiment of the present application, the conventional annealing method (left) and the appearance after annealing after adding a nitrogen device and an exhaust device after heat treatment in another embodiment (right). It can be seen intuitively that Figure 7 The hole transport layer / perovskite layer composite film that was annealed using the conventional annealing method had an uneven color and a whitening phenomenon after annealing, indicating that the annealing process was affected by the residual solvent or water vapor in the environment, resulting in the formation of some non-perovskite phases during the perovskite crystallization process, and the appearance was inconsistent with the normal perovskite phase; the perovskite layer / hole transport layer composite film after the nitrogen device and the exhaust device after heat treatment had a uniform appearance, indicating that the method of filling with nitrogen while sending away residual solvents and water vapor through the exhaust device can effectively avoid the interference of residual solvents and water vapor in the environment during the annealing process.

[0180] See also Figure 8 , Figure 8 The comparison results of the PL image of the hole transport perovskite stack prepared by the traditional method and the PL image of the perovskite layer / hole transport layer composite film prepared by an embodiment of the present application are shown in the figure. It can be seen intuitively that the brightness of the PL image of the comparative example is relatively low and uneven, indicating that the perovskite crystallization is relatively poor, which also confirms the previous conjecture that the annealing process is affected by residual solvents and water vapor to generate some non-perovskite phases, and the luminescence response of these non-perovskite phases is relatively poor, so they show lower brightness; the PL image of the perovskite layer / hole transport layer composite film of the present application is higher and uniform in brightness, indicating that the perovskite film crystallization quality obtained by the method of filling with nitrogen while sending away residual solvents and water vapor through an exhaust device is higher and more uniform.

[0181] 2. Battery performance characterization

[0182] Perovskite silicon-based laminated cells with a size of 166 mm×166 mm were prepared in the manner of Example 1 and Comparative Example 1, and the cell performance was tested. The test results are as follows:

[0183] Example 1

[0184]

[0185] Comparative Example 1

[0186]

[0187] According to the test results, the device conversion efficiency of the perovskite silicon-based tandem battery in Example 1 is normal, and is slightly improved compared with the battery effect prepared by the conventional method. It can be seen that when the perovskite layer / hole transport layer composite film prepared by the method of the present application is further used to prepare perovskite silicon-based tandem batteries, the expected device efficiency can be achieved, but the preparation steps are greatly simplified.

[0188] According to speculation, if a perovskite film is directly prepared on a silicon wafer substrate without a hole transport layer, the entire device is almost ineffective. Similarly, if a perovskite film is prepared on a silicon wafer substrate with a very thin hole transport layer, the conversion efficiency of the device is very low. However, if a perovskite film is prepared on a silicon wafer substrate with a hole transport layer of normal thickness, the conversion efficiency of the device is normal. Combined with the battery test results of Example 1, we speculate that the final hole transport layer of the composite film prepared by the method of the present application will form a thin layer structure at the buried interface of the perovskite, thereby achieving better battery conversion efficiency.

[0189] Based on the preparation principle of this preparation method, a part of the material constituting the hole transport layer is embedded in the crystal grain boundaries of the perovskite layer, and most of the remaining material is deposited at the interface of the perovskite layer. The hole transport layer / perovskite composite film is able to form a thin layer at the perovskite buried interface and form a relatively tight combination based on the principle of grain boundary embedding. Therefore, compared with the stacked cells obtained by traditional methods, the efficiency is slightly improved.

[0190] All documents mentioned in this application are cited as references in this application, just as each document is cited as reference separately. Unless they conflict with the application purpose and / or technical solution of this application, the cited documents involved in this application are cited with all contents and all purposes. When the cited documents are involved in this application, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the cited documents are involved in this application, the examples and preferred methods of the cited relevant technical features can also be incorporated into this application as references, but are limited to the implementation of this application. It should be understood that when the cited content conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0191] The technical features of the above-mentioned implementation modes and examples can be combined in any appropriate manner. To make the description concise, not all possible combinations of the technical features in the above-mentioned implementation modes and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0192] The above-described embodiments only express several implementation methods of the present application, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for those of ordinary skill in the art, without departing from the concept of the present application, several variations and improvements can also be made, which all belong to the protection scope of the present application. In addition, it should be understood that after reading the above-mentioned teaching content of the present application, those skilled in the art can make various changes or modifications to the present application, and the equivalent forms obtained also fall within the protection scope of the present application. It should also be understood that the technical solutions obtained by those skilled in the art on the basis of the technical solutions provided in the present application through logical analysis, reasoning or limited experiments are all within the protection scope of the claims attached to the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A perovskite layer / hole transport layer composite film, characterized in that: The perovskite layer / hole transport layer composite film is prepared by subjecting a mixed solution including a perovskite precursor material, a hole transport material and an organic solvent to a film-forming treatment and then to an annealing treatment, wherein the perovskite layer / hole transport layer composite film includes a perovskite layer and a hole transport layer adjacent to each other; in, The hole transport material includes an organic hole transport material; The perovskite layer composition includes ABX3 type perovskite material, wherein: the A-site ions include CH3NH3 + 、CH(NH2)2 + 、(CH3)2NH2 + , Cs + , Tl + Sc 3+ and Y 3+ At least one of; B site ions include Pb 2+ Sn 2+ ,Ge 2+ 、Ti 4+ and Zr 4+ At least one of; X-site ions include Br - ,I - , Cl - and SCN - At least one of .

2. The perovskite layer / hole transport layer composite film according to claim 1, characterized in that: The organic hole transport material is a carbazole phosphate hole transport material.

3. The perovskite layer / hole transport layer composite film according to claim 1, characterized in that: The thickness of the perovskite layer is 500nm-1200nm, and the thickness of the hole transport layer is 2nm-10nm.

4. The perovskite layer / hole transport layer composite film according to claim 1, characterized in that: The organic hole transport material comprises at least one of 2-(7H-dibenzo[c, g]carbazole-7-yl)ethylamine, 4-(7H-dibenzo[c, g]carbazole-7-yl)butylamine, 2-methoxy-2-(7H-dibenzo[c, g]carbazole-7-yl)ethylamine, 4-methoxy-4-(7H-dibenzo[c, g]carbazole-7-yl)butylamine and (4-(7H-dibenzo[c, g]carbazole-7-yl)butyl)phosphonic acid; and / or, The organic solvent includes at least one of dimethylformamide, dimethyl sulfoxide, acrylonitrile, N-methylpyrrolidone, butanediol, dimethylamine, dimethylimine and 2-methoxyethanol.

5. The perovskite layer / hole transport layer composite film according to any one of claims 1 to 4, characterized in that: The conditions of the annealing treatment include: The annealing treatment is carried out in a cavity having an exhaust system and an air inlet system, and heat-treated nitrogen is introduced through the air inlet system, and the gas containing water vapor and organic solvent in the cavity is discharged through the exhaust system; the heat-treated nitrogen refers to nitrogen with a temperature of 100°C to 150°C.

6. A method for preparing the perovskite layer / hole transport layer composite film according to any one of claims 1 to 5, characterized in that: include: Dissolving the perovskite precursor material and the hole transport material in the organic solvent to obtain a mixed solution; The mixed liquid is subjected to film-forming treatment to obtain a wet film; The wet film is subjected to annealing treatment to obtain a perovskite layer / hole transport layer composite film.

7. The preparation method according to claim 6, characterized in that: The step of preparing a wet film by subjecting the mixed liquid to a film-forming treatment comprises: The mixed liquid is subjected to film coating treatment to obtain a wet film; Optionally, the coating method includes at least one of inkjet printing, slit coating, blade coating and immersion; Optionally, the wet film has a thickness of 8 μm to 12 μm.

8. The preparation method according to claim 6, characterized in that: The step of preparing a perovskite layer / hole transport layer composite film by annealing the wet film comprises: Placing the wet film in a cavity having an air inlet system and an air exhaust system, wherein the air inlet system is used to pass the heat-treated nitrogen into the annealing cavity, and the air exhaust system is used to remove the gas containing water vapor and organic solvent in the cavity; The heat-treated nitrogen refers to nitrogen at a temperature of 100° C. to 150° C.

9. A perovskite silicon-based tandem solar cell, characterized in that: It comprises a silicon base cell, a perovskite top cell and an intermediate layer between the silicon base cell and the perovskite top cell, wherein the perovskite top cell comprises the perovskite layer / hole transport layer composite film and the functional layer according to any one of claims 1 to 5; Wherein, the velvet surface of the silicon substrate cell is adjacent to the intermediate layer; The hole transport layer in the perovskite layer / hole transport layer composite film is adjacent to the intermediate layer.

10. A method for preparing a perovskite silicon-based tandem solar cell, characterized in that: include: Prepare an intermediate layer on the velvet surface of the silicon substrate battery; The hole transport layer and the perovskite layer are prepared in one step on the intermediate layer by the preparation method according to any one of claims 6 to 8; The functional layers of the perovskite silicon-based tandem solar cell are sequentially prepared on the perovskite layer.